Global trends in myopia management attitudes and strategies in clinical practice – 2019 Update. Issue 1 (February 2020) - Wolffsohn, James S; Calossi, Antonio; Cho, Pauline; Gifford, Kate; Jones, Lyndon; Jones, Deborah; Guthrie, Sarah; Li, Ming; Lipener, Cesar; Logan, Nicola S; Malet, Florence; Peixoto-de-Matos, Sofia C.; et al.
Abstract: Purpose: A survey in 2015 identified a high level of eye care practitioner concern about myopia with a reported moderately high level of activity, but the vast majority still prescribed single vision interventions to young myopes. This research aimed to update these findings 4 years later. Methods: A self-administrated, internet-based questionnaire was distributed in eight languages, through professional bodies to eye care practitioners globally. The questions examined: awareness of increasing myopia prevalence, perceived efficacy of available strategies and adoption levels of such strategies, and reasons for not adopting specific strategies. Results: Of the 1336 respondents, concern was highest (9.0 ± 1.6; p < 0.001) in Asia and lowest (7.6 ± 2.2; p < 0.001) in Australasia. Practitioners from Asia also considered their clinical practice of myopia control to be the most active (7.7 ± 2.3; p < 0.001), the North American practitioners being the least active (6.3 ± 2.9; p < 0.001). Orthokeratology was perceived to be the most effective method of myopia control, followed by pharmaceutical approaches and approved myopia control soft contact lenses (p < 0.001). Although significant intra-regional differences existed, overall, most practitioners did not consider single-vision distance under-correction to be an effective strategy for attenuating myopia progression (79.6 %), but prescribed single vision spectacles or contact lenses as the primary mode of correction for myopic patients (63.6 ± 21.8 %). The main justifications for their reluctance to prescribe alternatives to single vision refractive corrections were increased cost (20.6 %) and inadequate information (17.6 %). Conclusions: While practitioner concern about myopia and the reported level of activity have increased over the last 4 years, the vast majority of eye care clinicians still prescribe single vision interventions to young myopes. With recent global consensus evidence-based guidelines having been published, it is hoped that this will inform the practice of myopia management in future.